2011
DOI: 10.1097/pcc.0b013e3181fe3925
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibition alters the inflammatory and fibrinolytic response to cardiopulmonary bypass in children*

Abstract: Objective Many children with a congenital heart defect undergo surgical correction requiring cardiopulmonary bypass (CPB). One sixth of these patients take an angiotensin-converting enzyme inhibitor (ACEi) for heart failure treatment. The effect of ACE inhibition on the fibrinolytic and inflammatory response in children undergoing CPB is unknown. In adults, ACE inhibition attenuates the increase in plasminogen activator inhibitor-1 (PAI-1) following CPB whereas the effect on the interleukin (IL)-6 response is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
12
1
1
Order By: Relevance
“…Techniques aimed to reduce the inflammatory surge associated with cardiac surgery have also been developed, since acute inflammation has been implicated in the development of postoperative kidney injury in some studies [8,26]. Consistent with these studies, we found that perioperative plasma concentrations of IL-6 and to a lesser extent IL-8 or IL-10 are associated with AKI.…”
Section: Discussionsupporting
confidence: 79%
“…Techniques aimed to reduce the inflammatory surge associated with cardiac surgery have also been developed, since acute inflammation has been implicated in the development of postoperative kidney injury in some studies [8,26]. Consistent with these studies, we found that perioperative plasma concentrations of IL-6 and to a lesser extent IL-8 or IL-10 are associated with AKI.…”
Section: Discussionsupporting
confidence: 79%
“…(31) In two small randomized trials in chronic ACE inhibitor users, postoperative PAI-1 concentrations were lower in patients continued on ACE inhibitor therapy compared to in patients whose ACE inhibitor was stopped prior to cardiac surgery. (13, 32) MR antagonists also reduce inflammatory cytokines and PAI-1 in normotensive or hypertensive subjects. (33, 34) In the present clinical trial, we observed the previously reported association between the inflammatory response to cardiac surgery and postoperative AF.…”
Section: Discussionmentioning
confidence: 99%
“…Fleming and co-workers also recently reported that concentrations of the inflammatory cytokines IL-6 and IL-8 were increased in the first postoperative day in children undergoing cardiac surgery randomized to an ACE inhibitor. (32) Activation of the kallikrein-kinin system contributes to both enhanced fibrinolysis and inflammation following cardiac surgery and, thus, potentiation of the kallikrein-kinin system could account for the increased intraoperative tissue-type plasminogen activator concentrations and increased postoperative inflammation observed in the ramipril group.…”
Section: Discussionmentioning
confidence: 99%
“…(15) Aminocaproic acid (antifibrinolytic), methylprednisolone and dexmedetomidine (alpha-2 agonist) were given intraoperatively at the discretion of the attending anesthesiologist. Briefly, the circuit was primed with a mixture of albumin and plasmalyte-A.…”
Section: Methodsmentioning
confidence: 99%